Synthesis and antinociceptive activity of novel mannich base derivatives of some new fused 3,5-pyrazolidinedione - Abhishek Tiwari; Anita Singh (Wolters Kluwer Medknow Publications, 2014)
In the present study, a novel series of mannich bases 1-((1-substituted ethyl-1H-benzo[d] imidazol-2-yl) methyl)-2-substituted phenylpyrazolidine-3,5-dione 3(a-l) were synthesized and evaluated as antinociceptive agents in mice by Eddy's hot plate and acetic acid-induced writhing models. The structures attributed to compounds 3a-3l were elucidated by using IR, 1H-NMR, and Mass spectroscopic techniques. Some compounds showed promising analgesic activity when compared with the standard drug Diclofenac sodium. Results of analgesic activity via hot plate model showed that compounds 3d and 3f were found to be more active than standard drug. Results of analgesic activity via acetic acid-induced writhing model showed that compounds 3a, 3c, 3k, and 3l showed activity which is comparable with the standard drug.